Use of water in the Mediterranean: sectorial distribution and prospects - Hamdy A.; Lacirignola C. (Aspects économiques de la gestion de l'eau dans le bassin méditerranéen, 1997)
In the arid and semi-arid regions of the Mediterranean, for all the practical purposes, fresh water resources are finite and most of the economically viable development of these resources has already been implemented. In addition, in those regions we are confronted with an increasing population and the associated expansion of urbanization and economic activities, all of which require more water and thus impose a tremendous strain on this already limited and fragile resource. Such prevailing conditions will automatically have their negative impacts on the sectorial water distribution and use creating a structural imbalance between the constantly increasing water demand to meet needs and the limited available water supply that normally will result in severe conflicts and competitions among the users. Nowadays the dilemma that the major developing countries of the region are facing is to balance demand and supply of water to ensure self-sufficiency in meeting agricultural, industrial and domestic water needs. Following the traditional technique of increasing the supply is questionable; most of the available water resources have been mobilized and very little can be done with the supplying side of water equation. The option we have is to manipulate the demand side for all the water use sectors, particularly the agricultural one which accounts for up to 80 per cent of water consumption. Irrigated agriculture has a particular responsibility and high potential for water saving. In the Mediterranean region there is no question on the crucial importance of demand management aiming at efficiency, equity and long-term water security making use of the tools that the legal and economic policy, the scientific and technological advancement have made available. It is fully realized that the economic tools alone will not be sufficient to tackle the sectorial water use imbalance. Technological solutions are of primary importance. To implement technological and economic tools and solutions, we need the institutional and human resource capacity and thus capacity building emerges as one of the key components. The interrelationship of all these components indicate the vital need to elaborate the concept of integrated demand management into implementable policies, programmes and actions. We have the chance to achieve our goals and we should not miss it
Atelier sur les Aspects Economiques de la Gestion de l'Eau dans le Bassin Méditerranéen, 1995/05/17-19, Marrakech (Morocco)